The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5897/jmpr11.1085
|View full text |Cite
|
Sign up to set email alerts
|

Difference in structure and complement fixing activity of pectic polysaccharides from different plant parts of Echinacea purpurea (L.) Moench.

Abstract: Water soluble pectic polysaccharide fractions were isolated from different parts of Echinacea purpurea in order to elucidate any structural and biological differences. Water extracts of stems, leaves, flower buds, open flowerheads, post fertile flowers and roots were purified by ion exchange chromatography and by gelfiltration. The polysaccharides consisted of a high amount of galacturonic acid, but also rhamnose, arabinose and galactose with glycosidic linkages compatible with rhamnogalacturonan type I (RG-I)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Yeast-derived particulate β -glucan (p- β -glucan) shows it has the ability to activate macrophages and dendritic cells via the dectin-1 pathway [ 42 ]. Pectic polysaccharides have certain complement activity that could improve immunity in vivo [ 43 ]. Experiments have demonstrated that the TNF- α produced after drug-induced rat peritoneal macrophage activation is dependently stimulated by acidic E. purpurea in a concentration (3.7 μ g/mL-500 μ g/mL) that could stimulate the activation of macrophages to secrete IFN- β 2 , while the E. purpurea acidic arabinogalactan could also dependently stimulate macrophage phagocytosis in the range of 20-200 μ g/mL [ 16 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yeast-derived particulate β -glucan (p- β -glucan) shows it has the ability to activate macrophages and dendritic cells via the dectin-1 pathway [ 42 ]. Pectic polysaccharides have certain complement activity that could improve immunity in vivo [ 43 ]. Experiments have demonstrated that the TNF- α produced after drug-induced rat peritoneal macrophage activation is dependently stimulated by acidic E. purpurea in a concentration (3.7 μ g/mL-500 μ g/mL) that could stimulate the activation of macrophages to secrete IFN- β 2 , while the E. purpurea acidic arabinogalactan could also dependently stimulate macrophage phagocytosis in the range of 20-200 μ g/mL [ 16 , 44 ].…”
Section: Discussionmentioning
confidence: 99%